Exposure to the Chinese Famine in Childhood Increases Type 2 Diabetes Risk in Adults. Issue 11 (14th September 2016) - Wang, Jing; Li, Yaru; Han, Xu; Liu, Bing; Hu, Hua; Wang, Fei; Li, Xiulou; Yang, Kun; Yuan, Jing; Yao, Ping; Miao, Xiaoping; Wei, Sheng; et al.
Abstract: Background: Evidence shows that exposure to poor conditions in early life is associated with an increased risk of chronic diseases in adults. Objective: We investigated whether exposure to the Chinese famine (1959–1961) in the fetal stage or in childhood (0–9 y) was associated with type 2 diabetes (T2D) and hyperglycemia in adulthood. Methods: We included 7801 subjects aged 56.4 ± 3.3 y from the Dongfeng-Tongji cohort. Subjects were classified into late-, middle-, and early-childhood–exposed, fetal-exposed, and unexposed groups. Excess mortality rate was used to evaluate the severity of famine. Logistic regression models were used to analyze the famine-dysglycemia associations. Generalized linear models were used to assess the famine effects on dysglycemia risk during the 5-y follow-up period among 3100 subjects. Results: In descriptive analyses, the risk of T2D was significantly greater in the middle-childhood–exposed group (OR: 1.44; 95% CI: 1.10, 1.87; P = 0.007), and the risk of hyperglycemia was higher in the middle- and late-childhood–exposed groups than in the unexposed group (OR: 1.54; 95% CI: 1.26, 1.88 and OR: 1.51; 95% CI: 1.23, 1.85, respectively). In sex-specific analyses, women exposed in middle childhood (OR: 1.55; 95% CI: 1.16, 2.06) and late childhood (OR: 1.40; 95% CI: 1.05, 1.87) had a higher risk of T2D than unexposed women. This association was not found in men. Similar associations were found for hyperglycemia risk. Moreover, subjects who experienced severe famine in childhood had a 38% higher T2D risk (95% CI: 1.05, 1.81) than those exposed to less severe famine. In retrospective cohort analyses, participants who experienced famine in middle childhood had a higher hyperglycemia risk relative to the unexposed group (RR: 2.06; 95% CI: 1.08, 3.90). Conclusion: Exposure to the Chinese famine in childhood was related to an increased risk of adulthood T2D and hyperglycemia, particularly in women.